2019
DOI: 10.1111/ncn3.12353
|View full text |Cite
|
Sign up to set email alerts
|

cTBS effect on language reorganization verified by fMRI and chronometry TMS in an aphasia patient

Abstract: The physiologic effect of continuous theta‐burst stimulation (cTBS) in language network has been reported, although it has the clinical benefit of longer‐lasting inhibitory effects with shorter stimulation time. We report 50‐year‐old aphasia patient showed increased activation of the left Broca's area by cTBS for 3 days on contralateral Broca's homologue area (Brodmann area 45) leading to improvements in speech performance. Furthermore, we were able to validate the engaged network and timing in picture naming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…This would indicate that the inhibitory effect of cTBS led to the recruitment of additional resources to achieve similar performance ( 12 16 ). Second, the inhibitory aftereffect of cTBS may have modulated intrahemispheric cortical connectivity; this explanation aligns with recent previous work done using TMS-EEG ( 32 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This would indicate that the inhibitory effect of cTBS led to the recruitment of additional resources to achieve similar performance ( 12 16 ). Second, the inhibitory aftereffect of cTBS may have modulated intrahemispheric cortical connectivity; this explanation aligns with recent previous work done using TMS-EEG ( 32 ).…”
Section: Discussionsupporting
confidence: 88%
“…Administering cTBS at 80% of AMT to the left pIFG has been reported to lead to no change in behavioral outcomes on a speech repetition task ( 33 ). Other studies have found that cTBS induced a significant decrease in pIFG and M1 effective connectivity during a listening task ( 34 ), suppressed activity in the left pIFG and increased activity in the right pIFG during repetition of words and pseudowords ( 22 ) and led to changes in interhemispheric and intrahemispheric TMS-evoked synchrony as measured by electroencephalogram (EEG) ( 32 ). In this study, since we used a higher intensity (90% of AMT), it is not surprising that we observed changes in the stimulated area and in the related network.…”
Section: Discussionmentioning
confidence: 99%